The Potential Prebiotic Berberine Combined With Methimazole Improved the Therapeutic Effect of Graves’ Disease Patients Through Regulating the Intestinal Microbiome - Han, Zhe; Cen, Chaoping; Ou, Qianying; Pan, Yonggui; Zhang, Jiachao; Huo, Dongxue; Chen, Kaining (Frontiers in Immunology, 2022)
Graves' disease, a typical metabolism disorder, causes diffuse goiter accompanied by ocular abnormalities and ocular dysfunction. Although methimazole (MI) is a commonly used drug for the treatment of GD, the efficacy of methimazole is only limited to the control of clinical indicators, and the side effects of MI should be seriously considered. Here, we designed a 6-month clinical trial that divided the patients into two groups: a methimazole group (n=8) and a methimazole combined with potential prebiotic berberine group (n=10). The effects of both treatments on thyroid function and treatment outcomes in patients with GD were assessed by thyroid index measurements and gut microbiota metagenomic sequencing. The results showed that the addition of berberine restored the patients' TSH and FT3 indices to normal levels, whereas MI alone restored only FT3. In addition, TRAb was closer to the healthy threshold at the end of treatment with the drug combination. MI alone failed to modulate the gut microbiota of the patients. However, the combination of berberine with methimazole significantly altered the microbiota structure of the patients, increasing the abundance of the beneficial bacteria Lactococcus lactis while decreasing the abundance of the pathogenic bacteria Enterobacter hormaechei and Chryseobacterium indologenes. Furthermore, further mechanistic exploration showed that the addition of berberine resulted in a significant upregulation of the synthesis of enterobactin, which may have increased iron functioning and thus restored thyroid function. In conclusion, methimazole combined with berberine has better efficacy in patients with GD, suggesting the potential benefit of berberine combined with methimazole in modulating the composition of intestinal microbes in the treatment of GD, providing new strong evidence for the effectiveness of combining Chinese and Western drugs from the perspective of modulating the intestinal microbiota.